LABOR SUPPLY FACTORS AND ECONOMIC FLUCTUATIONS. (2nd May 2018) - Foroni, Claudia; Furlanetto, Francesco; Lepetit, Antoine
Abstract: We propose a new Vector Autoregressive identification scheme that enables us to disentangle labor supply shocks from wage bargaining shocks. Identification is achieved by imposing sign restrictions on the responses of the unemployment rate and the labor force participation rate to the two shocks. According to our analysis on United States data over the period 1985–2014, labor supply shocks and wage bargaining shocks are important drivers of output and unemployment both in the short run and in the long run. These results suggest that identification strategies used in estimated new Keynesian models to disentangle labor market shocks may be misguided.